Impact of COVID-19 on Neonatal Outcomes : A Comprehensive Systematic Review - Lina Sriwaningsi; Ery Oktadiputra (The Indonesian Journal of General Medicine, 2024)
Background: Throughout the COVID-19 pandemic, pregnant women have been classified as a vulnerable population. However, the epidemiological evidence for infection risk during pregnancy on maternal and neonatal outcomes, such as preterm birth, hypertensive disorders in pregnancy, and postpartum hemorrhage of mothers and prematurity, respiratory and neurodevelopmental disorders of neonates, is still undetermined. The aim: The aim of this study to show about the impact of COVID-19 on neonatal outcomes. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Sciencedirect were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: The intrauterine transmission of SARS-CoV-2 was possible, although rare, with early postnatal transmission through direct contact with infected persons occurring more frequently.